The Article Deals with the Improvement of Professional Activity Efficiency of Operational Personnel for Boiler-Turbine Department of Power Stations - P. I. Dmitriev (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2012)
Human factor is one of the main determining factors in providing stability and reliability of power systems operation. In this context it is significant to estimate the level of professional activity efficiency of operational staff for boiler-turbine department of power stations.The article presents developed by the author algorithm of carrying out such research as well as the results of experimental research, carried out in one of the power stations of the state industrial unity “Belenergo” in order to show up the levels of professional activity efficiency of operational personnel (operator of central heat control panel of boilers, senior operator of boiler equipment) of turbo-boiler room.